Pengembangan Aplikasi Navigasi menggunakan Teknologi Augmented Reality pada Perangkat Smartphone berbasis Android (Studi Kasus: Jawa Timur Park 1 Malang) - Erika Ramadhanty; Herman Tolle; Komang Candra Brata (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Jawa Timur Park 1 is a tourist attraction located in the tourist town of Batu with an area of 8 hectares. For some people who have just visited Jawa Timur Park 1 for the first time, most will find it difficult to travel from one place to another in Jawa Timur Park 1 which can be rides or public places. The currently available solution today is by spreading maps of Jawa Timur Park 1 in several locations in Jawa Timur Park 1. However, the use of conventional maps is considered to be susceptible to causing errors in reading directions. In this research, a navigation application that is able to overcome this problem will be developed so that users can travel from one place to another more efficiently. The application will implement augmented reality technology with the help of ARCore SDK so that it allows users to understand the given directions more effectively and able to provide a different experience in navigating. The results of validation testing using the black box method produce a suitability value of 100% which indicates that all functions in the application can run as expected. Then the use of the application is considered capable of increasing the level of efficiency in terms of navigating time by 44,6%. While on usability testing related to the user satisfaction level, the application gets a value of 79,69 which indicate that the developed application is able to provide a good level of satisfaction to the user regarding the use of the application.